PENGENALAN SAINS PADA ANAK USIA DINI DI PAUD TERPADU SHABWA AMANAH LANDASAN ULIN UTARA KEC. LIANG ANGGANG KOTA BANJARBARU - Ratu Noor Khalidah; Nor Izzatil Hasanah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2020)
This study aims to determine the Introduction to Science in Early Childhood in Early Childhood Education Shabwa Amanah kindergarten of Ulin, Liang Anggang, Banjarbaru. The subjects in this study were 1 science introduction teacher and A group children consist 12 children. The data analysis in this research used Milles and Huberman which was conducted interactively using data consisting of reductions, presenting data, and conclusion (coding).Based on the results of this study indicate that the introduction of science in early childhood in Shabwa Amanah kindergarten of Ulin, Liang Anggang, Banjarbaru with introduces the concept of science in the form of mixing water with soap into small bubbles, sinking and floating, color changes and water absorption using 1) Demonstration method, the experimental method, the conversation method (question and answer), the assignment method, the play method, and the singing method. 2.) the media used are visual media in the form of realia media and audio-visual media using laptops and speakers 3.) The assessment given is in the form of assigning games to children, observing assessments, evaluating through conversation, as well as the children products .